THE STORY OF SACRIFICE IN THE QUR’AN AND THE BIBLE: JULIA KRESTEVA’S INTERTEXTUAL APPROACH - Zulfa, Nailatuz (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2022)
This paper discusses the story of the sacrifice carried out by Prophet Ibrahim in the Qur’an. The story in question is narrated in the Qur’an and the Bible. The story of Abraham’s sacrifice is significant in finding the similarities and differences between the two. Therefore, the approach used in this research is intertextual, initiated by Julia Kristeva, who tries to compare the narrative or interpretation between the two. Using this approach, many differences were found. This study concludes that the sacrifice narrated in the Qur’an by the author is divided into three fragments, the initial fragment, namely the sacrifice commandment, has the principle of expansion and haplology; the fragment of the sacrificial process itself has the principle of haplogy, and the last fragment is the principle of expansion and modification.